2020
DOI: 10.1111/gwat.13012
|View full text |Cite
|
Sign up to set email alerts
|

Using Wavelet Coherence to Characterize Surface Water Infiltration into a Low‐Lying Karst Aquifer

Abstract: Karstified carbonate aquifers may receive significant recharge contributions from losing streams, hence, the knowledge about surface water-groundwater (SW-GW) interactions is crucial with regard to water management (e.g., source protection zone delineation). The dynamics of SW-GW interactions may depend on factors such as the relative water levels between streams and aquifers, resulting in a temporal variation of exchange, which imposes complexity to the understanding of such dynamics. This study highlights th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Spring I revealed more consistent TCC results across the year with some slight elevated values during periods of zero effective rainfall in the summer. This small catchment (3.4 km 2 ) has no visible karst features of interest at the surface, and recent hydrological studies of the catchment have shown that under moderate recharge conditions the aquifer has a damped response to rainfall, but during higher sustained recharge conditions the spring becomes directly connected to a nearby river via a high level conduit, providing a much faster response to rainfall events (Schuler, 2020 ; Schuler et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Spring I revealed more consistent TCC results across the year with some slight elevated values during periods of zero effective rainfall in the summer. This small catchment (3.4 km 2 ) has no visible karst features of interest at the surface, and recent hydrological studies of the catchment have shown that under moderate recharge conditions the aquifer has a damped response to rainfall, but during higher sustained recharge conditions the spring becomes directly connected to a nearby river via a high level conduit, providing a much faster response to rainfall events (Schuler, 2020 ; Schuler et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This work has also exhibited the advantages of wavelet analysis over other types of signal analysis, particularly for temporally varying events. Recently, other studies such as Schuler et al (2021); Rodríguez-Murillo and Filella (2020); Lee and Kim (2019) have explored wavelet analysis and wavelet coherence as a tool for characterizing hydrological measurements (see Supporting Information). Future work could also include extending sensor coverage across the peninsula to create a more granular map of lag times.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the time-invariant limitations of some transfer function techniques when trying to reconstruct the temporal structure of relatively infrequent flow events such as floods or low water periods (Kuczera and Mroczkowski 1998;Labat et al 2000a), different numerical methods have been used to develop nonparametric transfer functions in order to capture nonlinear and nonstationary dynamics more accurately. These have included approaches more rooted in the spectral (frequency) domain (Larocque et al 1998;Labat et al 2000aLabat et al , 2002Bailly-Comte et al 2008) as well as time/frequency domains using wavelets (Labat et al 2000b(Labat et al , 2001Schuler et al 2020b). Machine learning approaches, for example artificial neural networks, have also been applied to karstic aquifers (Beaudeau et al 2001;Kurtulus and Razack 2007;Hu et al 2008).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Given the limitations highlighted in the previous models about the uncertainty in the diffuse recharge process, two catchments with long-term, high-resolution spring discharge time series were chosen, namely Ballindine and Manorhamilton (see section 'Materials and methods') in order to characterise the different flow components better by use of numerical techniques in both time and frequency domains on output signals (Schuler et al 2020b). The quantification of the relative contribution of these components, as well as their numerical representation, was attempted by analysing the three recharge components in the time and frequency domain.…”
Section: Characterise the Diffuse Component By Use Of Numerical Technmentioning
confidence: 99%